Zoonotic tuberculosis in Catalonia, Spain: Phylogenetic insights into Mycobacterium bovis and M. caprae transmission at the human-livestock interface - Bernat Pérez de Val; Enric Vidal; Tod Stuber; Jose Luís Sáez; María Teresa Tórtola (One Health)
This genomic epidemiology study analyzed Mycobacterium bovis and M. caprae isolates from animals and humans in Catalonia, Spain, between 2005 and 2023. Of 42 human tuberculosis (TB) cases, five were phylogenetically linked to livestock outbreaks, suggesting zoonotic transmission. The findings specifically indicate goats as a primary source of M. caprae transmission to humans. The study also revealed unexpected genetic diversity of mycobacteria within the same outbreak or even within the same patient, highlighting the complexity of tuberculosis transmission dynamics. The results underscore the value of genomic surveillance in understanding zoonotic TB transmission at the human-livestock interface and its role in informing effective control strategies.